The problem of tensions between the constitutional principle of freedom of speech and freedom of the press and the limits of access to information and publishing in Poland - Żukowski, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Although freedom of speech and freedom of the press are guaranteed by the norms of the Constitution and confirmed by international obligations, in practice the implementation of these norms encounters numerous difficulties. Practicing the profession of a journalist depends on the conditions of access to information, including public information. Access to public information can be classified as one of public subjective rights, so it is the legislator’s duty to shape the legal infrastructure in such a way as to create effective mechanisms that guarantee the transparency of the activities of public authorities, and thus the openness of public life. However, the regulations specifying the work of journalists are multi-level in nature and necessarily provide for numerous restrictions, causing tensions between the freedom of speech and other values guaranteed by the Constitution.
Keywords: constitution; freedom of speech; freedom of the press; journalist; journalism; information; public information; access to information